Kesalahan Penulisan Nama Jalan Menggunakan Arab melayu di Kota Pekanbaru - Dewi Sartika; Rofifah Zakiyah; Shendy Maftalia Fifadhilni (JURNAL EDUKASI NONFORMAL, 2022)
This study aims to analyze errors in writing Arabic-Malay used in writing street names in the city of Pekanbaru. The method we use in this study is the method of analysis (content analysis). Data collection techniques used in this study using documentation techniques, and writing techniques. The data analysis technique used in this research is Miles Huberman's analysis technique. The first step that the author takes is data reduction or classifying data, then the next step is presenting the data and the final step is making conclusions. The results of this study are that in writing street names as a whole there are 22 street nameplates, while incorrect writing amounts to 5 data with word errors such as the use of witness letters and word writing. While the correct writing amounted to 17 data. So it can be concluded that the writing used in naming street names is in a good category because there are more writings that comply with the Arabic-Malay writing guidelines.